ON THE MEANING OF RULE, PROHIBITING EVASION OF THE LAW IN PRIVATE INTERNATIONAL LAW - Maigul Nestayevna, Абилова (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2015)
This article is dedicated to the question of evasion of law, which is considered to be one of the main problems of private international law. The author analyzes the main theoretical approaches to this problem. Also the article provides an analysis of the issue in conflict regulation.